Sports and Entertainment Marketing Updated, Precision Exams Edition, 4th Edition - Ken Kaser; Dotty B. Oelkers (Cengage Learning, 2018)
SPORTS AND ENTERTAINMENT MARKETING, 4E incorporates feedback from instructors across the country. It includes expanded coverage, updated content, and exciting new features. The popular sports and entertainment topics continue to be the foundation for teaching marketing concepts. Each marketing function is incorporated throughout the text and is highlighted with an icon to indicate how it is used in the marketing process. Features throughout the textbook encourage students to relate marketing concepts to real-life businesses with exciting examples of famous athletes and celebrities while each chapter also offers a group project and preparation for BPA, DECA, and FBLA competitive events. MindTap for Sports and Entertainment Marketing Updated, Precision Exams Edition, 4th edition is the digital learning solution that helps teachers engage and transform today's students into critical thinkers. Through paths of dynamic assignments and applications that you can personalize, real-time course analytics and an accessible reader, MindTap helps you turn cookie cutter into cutting edge, apathy into engagement, and memorizers into higher-level thinkers. MindTap for this course includes the full, interactive eBook as well as auto-graded reading activities throughout the eBook for each lesson as well as student tools like flashcards, practice quizzes, and auto-graded homework and tests. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.